Lifting the Spin‐Momentum Locking in Ultra‐Thin Topological Insulator Films. Issue 11 (9th September 2021) - Leis, Arthur; Schleenvoigt, Michael; Cherepanov, Vasily; Lüpke, Felix; Schüffelgen, Peter; Mussler, Gregor; Grützmacher, Detlev; Voigtländer, Bert; Tautz, F. Stefan
Abstract: 3D topological insulators are known to carry 2D Dirac‐like topological surface states in which spin‐momentum locking prohibits backscattering. When thinned down to a few nanometers, the hybridization between the topological surface states at the top and bottom surfaces results in a topological quantum phase transition, which can lead to the emergence of a quantum spin Hall phase. Here, the thickness‐dependent transport properties across the quantum phase transition are studied on the example of (Bi0.16 Sb0.84 .)2 Te3 films, with a four‐tip scanning tunneling microscope. The findings reveal an exponential drop of the conductivity below the critical thickness. The steepness of this drop indicates the presence of spin‐conserving backscattering between the top and bottom surface states, effectively lifting the spin‐momentum locking and resulting in the opening of a gap at the Dirac point. The experiments provide a crucial step toward the detection of quantum spin Hall states in transport measurements. Abstract : When reducing the thickness of a topological insulator film, the topological surface states on the opposite faces of the thin film hybridize. Thickness‐dependent transport properties of such films are measured in situ by multi‐tip scanning tunneling microscopy. It is found that the hybridization is accompanied by the emergence of a spin‐conserving scattering mechanism, effectively lifting spin‐momentum locking in the film.